2015
DOI: 10.1007/978-4-431-55800-2_1
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and Point Defects in Silicon Materials

Abstract: This chapter aims to provide a basic understanding on the complex diffusion behavior of self-, dopant-, and selected metal atoms in silicon (Si). The complexity of diffusion in Si becomes evident in the shape of self-and foreign-atom diffusion profiles that evolves under specific experimental conditions. Diffusion studies attempt to determine from the diffusion behavior not only the mechanisms of atomic transport but also the type of the point defects involved. This information is of pivotal interest to contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 141 publications
1
5
0
Order By: Relevance
“…The dependences of fractional deviations (Δ) on 10 4 /T. Circles and triangles correspond to our data D SD (S-I-Y) 5) and Bracht group's data D SD (N), 37) respectively. A solid line and a dashed line are drawn for the eye's guide.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…The dependences of fractional deviations (Δ) on 10 4 /T. Circles and triangles correspond to our data D SD (S-I-Y) 5) and Bracht group's data D SD (N), 37) respectively. A solid line and a dashed line are drawn for the eye's guide.…”
supporting
confidence: 51%
“…We calculated the fractional deviations (Δ) for many data sets. Figure 3 shows the fractional deviations of our data 5) (given by circles: D SD (S-I-Y) = 0.90exp (-4.30 eV/k B T) + 6.9 × 10 2 exp(-4.8 eV/k B T)) and those of Bracht group's data 37) [triangles: D SD (N) = 0.5 × 2.7exp(-4.24 eV/k B T) + 0.7273 × 3.00 × 10 3 exp(-4.95 eV/k B T)], where 0.5 and 0.7273 are the correlation factors of a vacancy and an interstitial, respectively. Nakamura 33) adopted data from the Bracht group.…”
mentioning
confidence: 81%
“…They showed that the diffusion coefficient was decreased to about 70% by the hydrostatic pressure of 0.5 GPa in intrinsic Ge between 876-1086 K. It is well accepted that the self-diffusion in Ge crystals proceeds by a vacancy mechanism. 20 Here, we evaluate the thermal equilibrium V concentration, and compare the results with their experiment by assuming that only the change of V concentration by σ ex contributes to the change of self-diffusion coefficient in intrinsic Ge.…”
Section: Resultsmentioning
confidence: 99%
“…The high energy deposition by incident ions causes concentrations of defects X that are several orders of magnitude higher than their concentrations under thermal equilibrium. Self-diffusion in solids is controlled by the product of defect concentration and its diffusivity (cf., e.g., [ 36 ]). This shows that only mobile defects can contribute to IBIESD.…”
Section: Theoretical Investigations On the Mechanisms Of Ion Beam mentioning
confidence: 99%